How Many Americans Work Remotely? - Brynjolfsson, Erik,Horton, John J.,Makridis, Christos A.,Mas, Alexandre,Ozimek, Adam,Rock, Daniel,TuYe, Hong-yi (National Bureau of Economic Research, 2023)
Remote work surged during the Covid pandemic but there is disagreement about the extent of the change. To address this question, we field a new, nationally-representative survey: the Remote Life Survey (RLS). We find that in October 2020, 31.6 percent of the continuously employed workforce always worked from home (WFH) and 21.9 percent sometimes or rarely WFH, totaling 53.5 percent. We compare our results with alternative measurement approaches, with a focus on government surveys, and provide estimates on the impact of four factors: (a) differences among mail versus web-based survey respondents, (b) differences in the inclusion of self-employed workers, (c) the industry mix of the sample, and (d) the exclusion of people who were already remote pre-pandemic. We find that the last explanation (d) explains the bulk of the difference in estimates between the Current Population Survey (CPS) and other measures of remote work, with the CPS underestimating the remote work rate by up to 28 percentage points. Under our preferred estimates, we find that about half of the U.S. workforce worked remotely at least one day each week as of December 2020
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Telearbeit; Arbeitskräfte; Messung; Erhebungstechnik; Methodologie; USA; Health and Economic Development; Labor Force and Employment; Size; and Structure; Organization of Production; IT Management; Personnel Economics